Quality of reporting on birth defects in birth certificates: case study from a Brazilian reference hospital Qualidade da notificação de defeitos congênitos nas declarações de nascido vivo: estudo de caso em hospital de referência no Brasil - Daniela Varela Luquetti; Rosalina Jorge Koifman (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2009)
The aim of this study was to evaluate the coverage, validity and reliability of Brazil's Information System on Live Births (SINASC) for birth defects in a hospital in the city of Campinas (São Paulo State). The study population consisted of 2,823 newborn infants delivered in 2004 at the Women's Integrated Health Care Center (CAISM). A birth defect registry (ECLAMC) was used as the gold-standard. All birth defect cases reported at CAISM in 2004 (92 cases) were selected from SINASC data files. All 168 birth defect cases from the same city and year registered at ECLAMC were also retrieved. An underreporting of 46.8% was observed for all birth defects, and 36.4% when considering only the major birth defects. The ascertained sensitivity and specificity were, respectively, 54.2% and 99.8%. The reliability of three and four-digit ICD-10 coding for birth defects was 0.77 and 0.55 respectively (kappa statistic). These results suggest that information provided by birth certificates in Campinas still presents limitations when seeking to ascertain accurate estimates of the prevalence of birth defects, hence indicating the need for improvements in the SINASC database to enable it to portray birth defect prevalence at birth in this city. O presente estudo objetivou avaliar a cobertura, validade e confiabilidade do Sistema de Informações sobre Nascidos Vivos (SINASC) para anomalias congênitas, em hospital de Campinas, São Paulo, Brasil. A população de estudo consistiu nos 2.843 nascidos vivos do Centro de Atenção Integrada à Saúde da Mulher (CAISM), em 2004. Na base de dados SINASC, foram selecionados os 92 casos com diagnóstico de anomalia congênita no CAISM. Para o mesmo período, na base de dados ECLAMC, foram selecionados os 168 registros de nascidos vivos com anomalia congênita considerados como padrão-ouro, também no CAISM. Observou-se subnotificação de 46,8% para o conjunto dos casos de anomalias congênitas e de 36,4% quando a análise foi restringida para as anomalias congênitas maiores. A sensibilidade foi de 54,2%, e a especificidade, de 99,8%. Na análise da confiabilidade da codificação das anomalias congênitas, observou-se, para três e quatro dígitos da CID-10, um coeficiente kappa de 0,77 e 0,55, respectivamente. Esses resultados sugerem que o SINASC ainda apresenta limitações como fonte para a determinação da prevalência das anomalias congênitas e indicam que esse sistema demanda aprimoramento para retratar a situação desses casos em Campinas.